2011
DOI: 10.1007/s11357-011-9284-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP-sensitive potassium channels enhance angiotensin-induced oxidative damage and dopaminergic neuron degeneration. Relevance for aging-associated susceptibility to Parkinson’s disease

Abstract: Recent studies have shown that reninangiotensin system overactivation is involved in the aging process in several tissues as well as in longevity and aging-related degenerative diseases by increasing oxidative damage and inflammation. We have recently shown that angiotensin II enhances dopaminergic degeneration by increasing levels of reactive oxygen species and neuroinflammation, and that there is an aging-related increase in angiotensin II activity in the substantia nigra in rats, which may constitute a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 91 publications
4
32
0
Order By: Relevance
“…28 In cultures of dopaminergic neurons, we previously observed that inhibition of mitoKATP channels inhibits the AII-induced increase in O 2 − production. 29 Mitochondrial AT1 and AT2 receptors may play a major role in maintaining the integrity of this essential organelle against extra-mitochondrial insults, at least in the early moments, as observed in the present experiments with isolated mitochondria. Consistent with this, an increase in cell levels of oxidative stress (i.e.…”
Section: Discussionsupporting
confidence: 66%
“…28 In cultures of dopaminergic neurons, we previously observed that inhibition of mitoKATP channels inhibits the AII-induced increase in O 2 − production. 29 Mitochondrial AT1 and AT2 receptors may play a major role in maintaining the integrity of this essential organelle against extra-mitochondrial insults, at least in the early moments, as observed in the present experiments with isolated mitochondria. Consistent with this, an increase in cell levels of oxidative stress (i.e.…”
Section: Discussionsupporting
confidence: 66%
“…Our data showing that pretreatment with 5-HD significantly reversed the paclitaxel-induced decreases in SOCE implying that 5-HD may prevent chemotherapy-induced peripheral neuropathy by restoring [Ca 2þ ] i homeostasis in DRG neurons. The neuroprotective effect of 5-HD was shown previously in models of agingrelated neurodegenerative disease, in which 5-HD reduced angiotensin II-induced cell death in dopaminergic neurons (38). In the vascular system, 5-HD prevented the development of pulmonary hypertension by inhibiting TGF-b1 or MCP-1 signaling pathway (39).…”
Section: Discussionmentioning
confidence: 68%
“…The resulting overactivation of the RAS may exacerbate the microglial inflammatory response and produce oxidative stress, further contributing to the progression of dopaminergic neuron loss (Labandeira‐Garcia et al, ). Previous studies have shown that activation of AT1 receptors induces NADPH‐oxidase‐derived superoxide and subsequent enhancement of mitochondrial‐derived ROS, which leads to oxidative stress (Rey et al, ; Rodriguez‐Pallares et al, ; Zawada et al, ). AT1 and AT2 receptors and the NADPH‐oxidase complex have been found in both dopaminergic neurons and glial cells of rodents (Grammatopoulos et al, ; Joglar et al, ; Rodriguez‐Pallares et al, ) and primates (Garrido‐Gil et al, ), and the above mentioned AII‐induced activation of the NADPH‐oxidase complex may occur in neurons and/or glial cells.…”
Section: Discussionmentioning
confidence: 99%